Association of urine mitochondrial DNA with clinical measures of COPD in the SPIROMICS cohort - William Z. Zhang; Michelle C. Rice; Katherine L. Hoffman; Clara Oromendia; Igor Z. Barjaktarevic; J. Michael Wells; Annette T. Hastie; Wassim W. Labaki; Christopher B. Cooper; Alejandro P. Comellas; Gerard J. Criner; Jerry A. Krishnan; et al. (JCI Insight, 2024)
BACKGROUND Mitochondrial dysfunction, a proposed mechanism of chronic obstructive pulmonary disease (COPD) pathogenesis, is associated with the leakage of mitochondrial DNA (mtDNA), which may be detected extracellularly in various bodily fluids. Despite evidence for the increased prevalence of chronic kidney disease in COPD subjects and for mitochondrial dysfunction in the kidneys of murine COPD models, whether urine mtDNA (u-mtDNA) associates with measures of disease severity in COPD is unknown.METHODS Cell-free u-mtDNA, defined as copy number of mitochondrially encoded NADH dehydrogenase-1 (MTND1) gene, was measured by quantitative PCR and normalized to urine creatinine in cell-free urine samples from participants in the Subpopulations and Intermediate Outcome Measures in COPD Study (SPIROMICS) cohort. Urine albumin/creatinine ratios (UACR) were measured in the same samples. Associations between u-mtDNA, UACR, and clinical disease parameters — including FEV1 % predicted, clinical measures of exercise tolerance, respiratory symptom burden, and chest CT measures of lung structure — were examined.RESULTS U-mtDNA and UACR levels were measured in never smokers (n = 63), smokers without airflow obstruction (n = 107), participants with mild/moderate COPD (n = 139), and participants with severe COPD (n = 166). U-mtDNA was associated with increased respiratory symptom burden, especially among smokers without COPD. Significant sex differences in u-mtDNA levels were observed, with females having higher u-mtDNA levels across all study subgroups. U-mtDNA associated with worse spirometry and CT emphysema in males only and with worse respiratory symptoms in females only. Similar associations were not found with UACR.CONCLUSION U-mtDNA levels may help to identify distinct clinical phenotypes and underlying pathobiological differences in males versus females with COPD.TRIAL REGISTRATION This study has been registered at ClinicalTrials.gov ( NCT01969344).FUNDING US NIH, National Heart, Lung and Blood Institute, supplemented by contributions made through the Foundation for the NIH and the COPD Foundation from AstraZeneca/MedImmune, Bayer, Bellerophon Therapeutics, Boehringer-Ingelheim Pharmaceuticals Inc., Chiesi Farmaceutici S.p.A., Forest Research Institute Inc., GlaxoSmithKline, Grifols Therapeutics Inc., Ikaria Inc., Novartis Pharmaceuticals Corporation, Nycomed GmbH, ProterixBio, Regeneron Pharmaceuticals Inc., Sanofi, Sunovion, Takeda Pharmaceutical Company, and Theravance Biopharma and Mylan.